Handbook of research on impacts of international business and political affairs on the global economy - Norhayati Zakaria 1969-; Asmat-Nizam Abdul-Talib; Nazariah Osman (Business Science Reference, 2016)
"This book features dual perspectives on the business and political viewpoints for nations striving to maintain their economic standing in the era of globalization, providing insight into various economic factors impacting global businesses and international affairs"-- Provided by publisher.